PELATIHAN USAHA GUNA MENINGKATKAN PROFIT UMKM TANAMAN HIAS DAN OLEH-OLEH KHAS TAWANGMANGU DI DUSUN NGLURAH - Vika Yugi Kurniawan; Sutrima Sutrima; Siswanto Siswanto; Supriyadi Wibowo; Santoso Budi Wiyono (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service program was conducted by the Pure Mathematics & Application Research Group of the Mathematics Department, FMIPA UNS, with the aim of increasing the profits of ornamental plant and local specialty product SMEs in Nglurah Village, Tawangmangu District, Karanganyar Regency. The partner in this activity is the Farmers and SMEs Association located in Nglurah Village, Tawangmangu. The main issues faced by the partner are a lack of knowledge in modern business management, branding, and digital marketing, resulting in low product competitiveness in an increasingly competitive market. The solution offered includes intensive training on product processing, branding strategies, and digital marketing. The community service was implemented through a workshop attended by 30 participants, followed by a one-month mentoring period. The methodology included a participatory approach in needs assessment, theoretical and practical training, and direct mentoring in field implementation. The results showed significant improvements in participants' understanding of business management and their ability to utilize digital media for marketing. Several participants reported increased product visibility in online markets. This program is expected to have a long-term impact on the development of SMEs in Nglurah Village.